Room temperature nanoparticulate interfacial layers for perovskite solar cells via solvothermal synthesis - Savva, Achilleas; Papadas, Ioannis T.; Tsikritzis, Dimitris; Armatas, Gerasimos S.; Kennou, Stella; Choulis, Stelios A. (My University, 2017)
We present a solvothermal synthetic route to produce monodisperse CuO nanoparticles (NPs) in the range of 5-10 nm that can be used as a hole selective interfacial layer between indium tin oxide (ITO) and the perovskite active layer for p-i-n perovskite solar cells by spin casting the dispersions at room temperature. The bottom electrode interface modification provided by spherical CuO-NPs at room temperature promotes the formation of high quality perovskite photoactive layers with a large crystal size and strong optical absorption. Furthermore, it is shown that the nanoparticulate nature of the CuO hole transporting interfacial layer can be used to improve light manipulation within the perovskite solar cell device structure. The corresponding p-i-n CH3NH3PbI3-based solar cells show high V-oc values of 1.09 V, which is significantly higher compared to the V-oc values obtained with conventional PEDOT:PSS hole selective contact based perovskite solar cells.
Keywords: Inverted organic photovoltaics; Lead halide perovskite; Hole-Transporting layer; High performance; Oxide; Efficiency; Stability; Light; CUOX; CU2O